SYSTEMATIC REVIEW TECHNICAL AND VOCATIONAL EDUCATION AND TRAINING AS HUMAN CAPITAL DEVELOPMENT STRATEGY IN SMES INDONESIA - Sundjoto Sundjoto (SEAN Institute, 2023)
Small and medium enterprises (SMEs) are one of the most important and important areas in the Indonesian financial system. SMEs play an important role in shaping national expansion strategies, employment technology and social suitability by improving housing distribution of vulnerable segments of society collaborating in Technical and Vocational Education and Training as Human Capital Development strategy in Indonesia. In the maximum number of countries, TVET represent more than 90% of all companies and contribute on a scale closer to overall economic growth. The authorities are not only increasing their efforts to promote a quarter of SMEs, but are also paying attention to SMEs. This research used the qualitative method with systematic review approach. TVET as Human Capital Development strategy accumulate the scope is intended to provide a long-term framework for the advancement of the SME sector and a legitimate implementation mechanism that can provide a favorable environment for the economic growth of cohesive enterprises.